1998
DOI: 10.1212/wnl.51.4.1219
|View full text |Cite
|
Sign up to set email alerts
|

Devic's neuromyelitis optica: A prospective study of seven patients treated with prednisone and azathioprine

Abstract: Seven newly diagnosed patients with Devic's neuromyelitis optica were treated with long-term prednisone and azathioprine, and were followed every 2 months for at least 18 months. Their Expanded Disability Status Scale score improved significantly (mean at baseline, 9; mean at 18 months, 3; p < 0.005), and no relapses occurred for more than 18 months. Multicenter controlled studies are needed to prove the efficacy of this therapeutic regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
186
0
25

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(222 citation statements)
references
References 2 publications
11
186
0
25
Order By: Relevance
“…In those with relapsing disease, lifelong therapy should be considered (2). Prednisone, azathioprine, and mycophenolate mofetil have all been effective in disease stabilization and relapse reduction in uncontrolled trials of NMO (41)(42)(43). The use of rituximab has been successful in a case series of patients with resistant disease (44).…”
Section: Discussionmentioning
confidence: 99%
“…In those with relapsing disease, lifelong therapy should be considered (2). Prednisone, azathioprine, and mycophenolate mofetil have all been effective in disease stabilization and relapse reduction in uncontrolled trials of NMO (41)(42)(43). The use of rituximab has been successful in a case series of patients with resistant disease (44).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies including a total of almost 400 patients have shown that AZA reduces the ARR, sometimes associated with improvement of neurological disability [17,[74][75][76][77][78][79][80]. A retrospective study evaluating classical NMO and patients with AQP4-IgG-positive NMOSD reported a decrease in the mean ARR from 2.18 to 0.64 in 70 patients treated with AZA for >1 year, with or without concomitant corticosteroid therapy [77].…”
Section: Azamentioning
confidence: 99%
“…Adjunctive therapy of AZA [17,75,77,79], MMF [79,83], MTX [85][86][87], ciclosporine A [88], and tacrolimus [89] with oral corticosteroids have all been reported to be (partly) effective and safe in NMOSD. In breakthrough disease intermittent TPE might be added to immunosuppressive treatment [8,98], but usually escalation to a biological is preferable.…”
Section: Combination Therapies Of Immunosuppressantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination therapy with a corticosteroid and azathioprine is the current standard treatment for preventing NMO relapse [5]; however, some patients are refractory to it.…”
mentioning
confidence: 99%